Scale-dependent effects of roadways on the movement behavior of a large-bodied pit viper (Crotalus horridus) - Tipton, Anna F.; Vázquez-Diosdado , Jorge A.; DeSantis, Dominic L. (Frontiers in Ecology and Evolution, 2023)
Roadways are among the most widespread and disruptive anthropogenic land use features that influence the behavior and movement of wildlife. Negative impacts of roadways have been well documented, but the behavioral impact of roadways on smaller, cryptic species has yet to be thoroughly examined. Using a novel integration of radio telemetry and tri-axial accelerometry, we evaluated the effects of roadways on the movement behavior of 26 adult Timber Rattlesnakes (Crotalus horridus) at coarse and fine time scales in central Georgia between June 2020 and November 2021. To interpret the effect of roads at a coarse time scale, we modeled the effect of mean annual distance to roadways (DTR) on annual measures of movement and space use by C. horridus using both radio telemetry and accelerometry derived metrics (RT and ACT metrics). To explore the fine-scale impact of roadways, we quantified RT and ACT metrics during confirmed road interactions (i.e., instances when individual snakes crossed a road or encountered a road but did not cross) and compared these instances to the RT and ACT metrics calculated across the remainder of the active season within this subset of snakes. Relating the annual RT and ACT metrics to DTR revealed no significant associations at a coarse time scale. However, the evaluation of C. horridus movement behavior during punctuated road encounters revealed that snakes increased RT and ACT metrics during the road interactions compared to metrics calculated across the remainder of the active season. This might indicate that the abundance of contiguous habitat adjacent to roadways at our study site is serving as an adequate buffer to any long-term shifts in movement behavior, but the potential hidden cost of increasing movement when snakes encounter roads could have negative implications for populations that encounter roads more frequently, even in the absence of significant direct road mortality. Overall, integrating radio telemetry and accelerometry and adopting a scale-dependent approach to quantifying movement allowed for a more detailed evaluation of the response of C. horridus to roadways. This approach holds promise for detecting and interpreting previously overlooked short-term alterations in snake movement behavior with potentially significant fitness consequences.